ORGANIZATIONAL-PEDAGOGICAL CONDITIONS OF DEVELOPMENT OF LEADERSHIP POTENTIAL OF THE HEAD OF THE EDUCATIONAL ORGANIZATION - I. Koksnikova; I. Lilienthal (Вестник Северо-Кавказского федерального университета, 2022)
The Central issue ofthe article is the theoretical and empirical study ofthe possibilities of developing the leadership potential of the head of an educational organization. The authors give the main approaches to the problem, reveal the essence of the concept of "leadership potential", describe the components of the leadership potential of the head. The article presents the data of ascertaining experiment parameters of leadership potential of the management of educational organizations (for example, schools). It is shown that the creation of special organizational and pedagogical conditions can contribute to the development of leadership potential of the heads of educational organizations.